If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -34 = (x + 2)(x + -5) Reorder the terms: -34 + x = (x + 2)(x + -5) Reorder the terms: -34 + x = (2 + x)(x + -5) Reorder the terms: -34 + x = (2 + x)(-5 + x) Multiply (2 + x) * (-5 + x) -34 + x = (2(-5 + x) + x(-5 + x)) -34 + x = ((-5 * 2 + x * 2) + x(-5 + x)) -34 + x = ((-10 + 2x) + x(-5 + x)) -34 + x = (-10 + 2x + (-5 * x + x * x)) -34 + x = (-10 + 2x + (-5x + x2)) Combine like terms: 2x + -5x = -3x -34 + x = (-10 + -3x + x2) Solving -34 + x = -10 + -3x + x2 Solving for variable 'x'. Reorder the terms: -34 + 10 + x + 3x + -1x2 = -10 + -3x + x2 + 10 + 3x + -1x2 Combine like terms: -34 + 10 = -24 -24 + x + 3x + -1x2 = -10 + -3x + x2 + 10 + 3x + -1x2 Combine like terms: x + 3x = 4x -24 + 4x + -1x2 = -10 + -3x + x2 + 10 + 3x + -1x2 Reorder the terms: -24 + 4x + -1x2 = -10 + 10 + -3x + 3x + x2 + -1x2 Combine like terms: -10 + 10 = 0 -24 + 4x + -1x2 = 0 + -3x + 3x + x2 + -1x2 -24 + 4x + -1x2 = -3x + 3x + x2 + -1x2 Combine like terms: -3x + 3x = 0 -24 + 4x + -1x2 = 0 + x2 + -1x2 -24 + 4x + -1x2 = x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -24 + 4x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. 24 + -4x + x2 = 0 Move the constant term to the right: Add '-24' to each side of the equation. 24 + -4x + -24 + x2 = 0 + -24 Reorder the terms: 24 + -24 + -4x + x2 = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -4x + x2 = 0 + -24 -4x + x2 = 0 + -24 Combine like terms: 0 + -24 = -24 -4x + x2 = -24 The x term is -4x. Take half its coefficient (-2). Square it (4) and add it to both sides. Add '4' to each side of the equation. -4x + 4 + x2 = -24 + 4 Reorder the terms: 4 + -4x + x2 = -24 + 4 Combine like terms: -24 + 4 = -20 4 + -4x + x2 = -20 Factor a perfect square on the left side: (x + -2)(x + -2) = -20 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 5(-9-3d)= | | 1.5x^2+0.5x=3 | | -144=-4(1-7m) | | 2x+4(3x+17)=152 | | 3sinx+y^3=5x^2 | | -34=(x+2)(x-5) | | 9x=8x+32 | | (P+5)+2= | | 12x-12=4x+28 | | -140=4x-2(-4x+10) | | 5x-15+2=-13+5x | | 3(x+1)1+2x=2(2x+2)+x | | 6y+4x=8 | | (7x+3)+(x-5)=-16 | | (7x+3)+(a-5)=-16 | | -93=7x-6(x+14) | | 3(-2)+y=4 | | 3-5x=-6x+5 | | 9x+1=21x+1 | | 0=-5x+(-10) | | 44=-4x-4(-3x+7) | | 9x-9=4x+16 | | 9x-9=4x | | 112=-8(m-4) | | p+(p+15)=2p+15 | | 5-y=x | | 7x+5(-2x+3)=42 | | 8(k+1)=8(1+10k) | | 9x-9=4x-16 | | -80=-8-9x | | sec(4x)=2 | | -19=-7x+2(4x-7) |